ELIMINATION OF ERRORS IN CODEWORDS ACCORDING TO THE RESULTS OF PARITY CHECKING - A. S. Poljakov; V. E. Samsonov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
An algorithm for finding wrong symbols in codewords based on using the results of checking for parity on axes and main diagonal of code plane is proposed. This algorithm allows to find the single errors and, under certain conditions, the group errors in the lines and columns of code plane.